Wordwall as An Interactive Media For Science Learning In Primary Schools Literature Study: (2020-2025) - Lika Aprilia; Noening Andrijati; Bambang Subali; Nuni Widiarti (Universitas Negeri Yogyakarta, 2026)
This study aims to examine the use of Wordwall as an interactive learning medium in Natural and Social Sciences (IPAS) learning at the primary school level. The research employed a Systematic Literature Review (SLR) design to identify, screen, and synthesize relevant studies published between 2020 and 2025. Articles were retrieved from several academic databases, including Google Scholar, SINTA, DOAJ, and ResearchGate, using the Publish or Perish software. The selection process was conducted based on predefined inclusion criteria focusing on empirical studies related to Wordwall implementation in primary education. A total of 20 studies met the eligibility criteria and were further analyzed. In addition to qualitative synthesis, bibliometric mapping using VOSviewer was conducted to visualize keyword co-occurrence, thematic clusters, and research trends. The findings indicate that most of the reviewed studies report positive associations between the use of Wordwall and increased student motivation, engagement, and conceptual understanding in science-related subjects. However, variations in research design, sample characteristics, and outcome measures were observed across studies. Therefore, the conclusions drawn in this review are limited to the patterns identified in the selected literature. Overall, the results suggest that Wordwall has potential as an interactive digital medium to support primary science learning, while further rigorous empirical studies are recommended to strengthen the evidence base.